2016
DOI: 10.1530/rep-15-0375
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa telomeres determine telomere length in early embryos and offspring

Abstract: Offspring telomere length (TL) has been correlated with paternal TL, but the mechanism for this parent of origin-specific inheritance remains unclear. The objective of this study has been to determine the role of spermatozoa TL in embryonic telomere lengthening by using two mouse models showing dimorphism in their spermatozoa TL: Mus musculus vs Mus spretus and old vs young Mus musculus. Mus spretus spermatozoa displayed a shorter TL than Mus musculus. Hybrid offspring exhibited lower TL compared with Mus musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 31 publications
3
53
2
1
Order By: Relevance
“…What’s more, the sperm with short telomeres derived from the late generation of telomerase-null mice (TR −/− ) would have some bad influence on the fertilization and embryonic development, More specifically, fertilization of TR −/− sperm with wild-type eggs exhibited low rates of cleavage and development to morula and blastocysts14. Moreover, our previous study demonstrated a positive correlation between the telomere length and embryo quality in the early stages of development15, and another study reported that spermatozoa telomeres determine the telomere length of early embryos and offspring16. A recent report also showed that the STL could be used as a new parameter in diagnosing infertility in males17.…”
mentioning
confidence: 99%
“…What’s more, the sperm with short telomeres derived from the late generation of telomerase-null mice (TR −/− ) would have some bad influence on the fertilization and embryonic development, More specifically, fertilization of TR −/− sperm with wild-type eggs exhibited low rates of cleavage and development to morula and blastocysts14. Moreover, our previous study demonstrated a positive correlation between the telomere length and embryo quality in the early stages of development15, and another study reported that spermatozoa telomeres determine the telomere length of early embryos and offspring16. A recent report also showed that the STL could be used as a new parameter in diagnosing infertility in males17.…”
mentioning
confidence: 99%
“…A previous study suggested that the ALT mechanism could be active during spermatogenesis in humans, based on an unexpected age‐related increase in sperm TL in the absence of telomerase (Antunes et al, ). This mechanism has been described also in the absence of telomerase activity after oocyte fertilization and activation (de Frutos et al, ; Liu et al, ). Interestingly, we observed upregulation of Zscan4 in old mouse testicles, and ZSCAN4 protein was localized in the nucleus of spermatocytes and spermatids, pointing to an active ALT mechanism during meiotic and postmeiotic stages.…”
Section: Discussionmentioning
confidence: 71%
“…It could be that longer telomeres in the sperm of old males somehow compensate for the short telomeres of aged oocytes. Further, it has been also described that sperm telomeres act as guides for intratelomeric alternative telomere lengthening of the early embryo's telomeres after fertilization (de Frutos et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations